Efektivitas Pelaksanaan Pelayanan Administrasi Terpadu Kecamatan (Paten) Di Kecamatan Mandau Kabupaten Bengkalis - Amelia putri; Harapan Tua RFS (Jurnal Ilmu Sosial dan Ilmu Politik, 2026)
Integrated District Administrative Service (PATEN) is a public service policy established under the Regulation of the Minister of Home Affairs Number 4 of 2010. The implementation of PATEN is expected to simplify bureaucratic procedures and improve public satisfaction with government services. However, its implementation in Mandau Sub-district, Bengkalis Regency, continues to face several challenges, including the suboptimal functioning of the information desk, inadequate supporting facilities and infrastructure, delays in service completion under certain conditions, and public complaints regarding the quality of services provided. The fluctuating service volume from year to year also indicates inconsistencies in the implementation of PATEN in practice. This study aims to analyze the effectiveness of PATEN implementation in Mandau Sub-district, Bengkalis Regency, and to identify the factors that hinder its implementation. The study employed a qualitative method using a case study approach. Data were collected through semi-structured interviews, direct observation, and documentation involving officials of the Mandau Sub-district Office and members of the public who used PATEN services. Data validity was ensured through source triangulation, technique triangulation, and time triangulation. The analysis was conducted using Agus Dwiyanto's public service effectiveness indicators, namely productivity, service quality, responsiveness, responsibility, and accountability. The findings indicate that the implementation of PATEN in Mandau Sub-district has generally been quite effective in meeting the administrative needs of the community, although it has not yet been fully optimized. Four main inhibiting factors were identified: limited operational funding, dependence on the availability of structural officials for document approval and signatures, suboptimal utilization of information technology in the service process, and the public's limited understanding of the applicable service procedures and requirements.